Pengaruh Visual Content Marketing dan Electronic Word of Mouth terhadap Perceived Quality serta Dampaknya pada Intention to Recommend pada Pengguna Jasa Titip Online - Kurnia Dyah Ayu (ARZUSIN, 2026)
Digital transformation is driving changes in marketing strategies, particularly through the use of visual content marketing and electronic word of mouth (e-WOM) in shaping consumer perceptions. In the context of online jasa titip services, visual content and consumer reviews are crucial factors in building perceived quality, which subsequently influences intention to recommend. This study aimed to analyze the effect of visual content marketing and e-WOM on perceived quality and its impact on intention to recommend among users of the @syazaofficial jasa titip service among university students in Semarang City. The study employed a quantitative approach with a correlational research design, with data collected through an online questionnaire administered to 100 respondents selected using purposive sampling. Data were analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The results showed that visual content marketing and e-WOM had a positive and significant effect on perceived quality. In addition, perceived quality was found to have a positive effect on intention to recommend and to function as a mediating variable in the relationship between visual content marketing and e-WOM and intention to recommend. These findings underscore the importance of managing engaging visual content and fostering positive e-WOM to enhance perceived quality and encourage consumers to provide recommendations. The practical implications of this study offer guidance for jasa titip service providers in designing effective digital marketing strategies based on visual content and consumer interactions.